2022
DOI: 10.1101/2022.12.12.520054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Coexisting morpho-biotypes unveil the regulatory bases of phenotypic plasticity in pancreatic ductal adenocarcinoma

Abstract: Intratumor morphological heterogeneity predicts clinical outcomes of pancreatic ductal adenocarcinoma (PDAC). However, it is only partially understood at the molecular level and devoid of clinical actionability. In this study we set out to determine the gene regulatory networks and expression programs underpinning intra-tumor morphological variation in PDAC. To this aim, we identified and deconvoluted at single cell level the molecular profiles characteristic of morphologically distinguishable clusters of PDAC… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Recently, Krebs and colleagues showed the enrichment of axon guidance-associated gene sets in basal-like as well as high grade PDAC [15]. Furthermore, neuronal-like progenitor cell states have been reported in undifferentiated tumors [16] and positively selected in post-treatment tumors [17]. Most of the previous studies have focused on investigating the role of members of the Slit/Robo axis on the PDAC malignant traits of PDAC as well as its cell identity [15, 18, 19, 20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Krebs and colleagues showed the enrichment of axon guidance-associated gene sets in basal-like as well as high grade PDAC [15]. Furthermore, neuronal-like progenitor cell states have been reported in undifferentiated tumors [16] and positively selected in post-treatment tumors [17]. Most of the previous studies have focused on investigating the role of members of the Slit/Robo axis on the PDAC malignant traits of PDAC as well as its cell identity [15, 18, 19, 20, 21].…”
Section: Introductionmentioning
confidence: 99%
“…For pancreatic cancer we employed a new classification of TCGA samples using a multi- class classifier already implemented to classify three novel PDAC subtypes (Glandular, GL; Transitional, TR; Undifferentiated, UN) obtained from the transcriptional profiles of multiple morphological distinguishable tumor areas isolated by laser micro-dissection (LMD) in primary PDACs of treatment-naïve patients 52 . Briefly, a random Forest (RF) classification method was used to build the model setting the number of trees to 500.…”
Section: Methodsmentioning
confidence: 99%
“…Transitional, TR; Undifferentiated, UN) obtained from the transcriptional profiles of multiple morphological distinguishable tumor areas isolated by laser micro-dissection (LMD) in primary PDACs of treatment-naïve patients 52 . Briefly, a random Forest (RF) classification method was used to build the model setting the number of trees to 500.…”
Section: Transcriptomics Datasetmentioning
confidence: 99%
“…[14][15][16] Recently, Krebs et al showed the enrichment of axon guidance-associated gene sets in basal-like as well as high-grade PDAC. 17 Furthermore, neuronal-like progenitor cell states have been reported in undifferentiated tumours 18 and are positively selected in posttreatment tumours. 12 Most of the previous studies have focused on investigating the role of members of the Slit/Robo axis on the PDAC malignant traits as well as its cell identity.…”
Section: Pancreasmentioning
confidence: 99%